Effects of Surfactants on the Properties of Mortar Containing Styrene/Methacrylate Superplasticizer - El-Sayed Negim; Latipa Kozhamzharova; Jamal Khatib; Lyazzat Bekbayeva; Craig Williams (The Scientific World Journal)
The physical and mechanical properties of mortar containing synthetic cosurfactants as air entraining agent are investigated. The cosurfactants consist of a combination of 2% dodecyl benzene sodium sulfonate (DBSS) and either 1.5% polyvinyl alcohol (PVA) or 1.5% polyoxyethylene glycol monomethyl ether (POE). Also these cosurfactants were used to prepare copolymers latex: styrene/butyl methacrylate (St/BuMA), styrene/methyl methacrylate (St/MMA), and styrene/glycidyl methacrylate (St/GMA), in order to study their effects on the properties of mortar. The properties of mortar examined included flow table, W/C ratio, setting time, water absorption, compressive strength, and combined water. The results indicate that the latex causes improvement in mortar properties compared with cosurfactants. Also polymer latex containing DBSS/POE is more effective than that containing DBSS/PVA.